Association with outcomes and response to treatment of trimethylamine N‐oxide in heart failure: results from BIOSTAT‐CHF. (29th October 2018) - Suzuki, Toru; Yazaki, Yoshiyuki; Voors, Adriaan A.; Jones, Donald J.L.; Chan, Daniel C.S.; Anker, Stefan D.; Cleland, John G.; Dickstein, Kenneth; Filippatos, Gerasimos; Hillege, Hans L.; Lang, Chim C.; Ponikowski, Piotr; et al.
Abstract : Aims: Association of elevated circulating levels of trimethylamine N‐oxide (TMAO) with adverse outcomes in patients with heart failure (HF) has been described. However, response of TMAO levels to treatment and medications has not been investigated. Therefore, we investigated whether TMAO levels are responsive to guideline‐recommended treatment and medications, and further reflect changes in outcomes. Methods and results: TMAO levels were investigated in the systems BIOlogy Study to TAilored Treatment in Chronic Heart Failure (BIOSTAT‐CHF), which addressed response to guideline‐recommended pharmacological treatment. TMAO levels in 2234 patients with new‐onset or progressively worsening HF showed strong associations with adverse events (mortality and/or rehospitalisation) at 1, 2 and 3 years [hazard ratio (HR) 1.37–1.51, P ≤ 0.019). Analysis of 972 patients with plasma available at both enrolment and follow‐up visit showed reductions of B‐type natriuretic peptide (BNP) levels with guideline‐based treatment ( P < 0.001), but not for TMAO levels. Moreover, patients with higher TMAO levels than median before and after treatment showed increased association with adverse outcomes [HR 2.21, 95% confidence interval (CI) 1.43–3.43, P < 0.001] compared to patients with lower than median levels either before or after treatment (HR 1.13, 95% CI 0.63–2.04, P = 0.684 and HR 1.14, 95% CI 0.64–2.03, P = 0.662, respectively). Conclusion: TMAO levels were associated with adverse outcomes (mortality and/or rehospitalisation) in BIOSTAT‐CHF, and did not respond to guideline‐based pharmacological treatment in contrast to BNP levels which did as expected. Lower TMAO levels were associated with favourable outcome regardless of treatment.